Pengaruh Good Corporate Governance, Likuiditas Dan Firm Size Terhadap Pengungkapan Tanggung Jawab Sosial PT. Pertamina (Persero) - Rahmayanti, Octaviannisa; Armin, Rini; Verlandes, Yuliasnita (Philosophiamundi, 2024)
CSR is one of the company's initiatives as a form of responsibility in overcoming social disparities and environmental impacts arising from the company's operational activities. CSR disclosure is generally found in the company's sustainability report. The purpose of this study is to examine whether there is a relationship between GCG (with measurements of the audit committee and independent commissioners), liquidity, and company size with CSR disclosure at PT Pertamina (Persero). The data used are secondary data from the sustainability report of PT Pertamina (Persero) from 2018 to 2023 which are accessed through the company's website. The research method applied is multiple regression analysis using SPSS 22 software for data analysis. The results of the study indicate that GCG, liquidity, and company size do not have a significant effect on CSR disclosure at PT Pertamina (Persero)